The Effect of Honey on Lowering Blood Pressure in Hypertension Elderly at Werdha Theodora Nursing Home, Makassar - Ngutro, Rania Hairunnisa; Mokhtar, Shulhana; Khalid, Nur Fadhillah; Royani, Ida; Kanang, Indah Lestari Daeng (Jurnal Biologi Tropis, 2024)
Hypertension is a risk factor that contributes to the development of stroke, heart failure, myocardial infarction and kidney failure. Even though in some cases the symptoms can be found, there are quite a few who think of it as just an ordinary disorder so they realize too late that hypertension is affected. This study aims to determine the effectiveness of giving honey in reducing blood pressure in elderly people with hypertension at the Theodora Makassar Nursing Home. This type of research is experimental with a cross-sectional design. The sampling technique was purposive sampling for 7 research subjects. Data was collected through primary data measuring blood pressure before and after administering forest honey with and/or without antihypertensive medication. The statistical test used is the paired T test. The results showed that the average systolic blood pressure before giving honey was 143.28 mmHg and after giving honey 134.14 mmHg. Then the diastolic blood pressure before honey was 82.14 mmHg and after honey 71.85 mmHg. The average systolic and diastolic blood pressure after administering honey was 134.14 mmHg and 71.85 mmHg. The statistical test results obtained a p-value of 0.018 for systolic blood pressure and a p-value of 0.011 for diastolic blood pressure (p<0.05). The conclusion is that giving honey is effective in reducing blood pressure in elderly people suffering from hypertension at the Theodora Makassar Nursing Home.